Asymmetric Ugi 3CR on isatin-derived ketimine: synthesis of chiral 3,3-disubstituted 3-aminooxindole derivatives - Lesma, Giordano; Meneghetti, Fiorella; Sacchetti, Alessandro; Stucchi, Mattia; Silvani, Alessandra (Beilstein Journal of Organic Chemistry, 2014)
An efficient Ugi three-component reaction of a preformed chiral ketimine derived from isatin with various isonitrile and acid components has been developed. The reactions proceeded smoothly and in a stereocontrolled manner with regard to the new center of the Ugi products due to the stereoinduction of the amine chiral residue. A wide variety of novel chiral 3,3-disubstituted 3-aminooxindoles were obtained, a selection of which were subjected to post-Ugi transformations, paving the way to application as peptidomimetics.
Keywords: isatin; multicomponent; oxindole; peptidomimetics; Ugi